Loop-Mediated Isothermal Amplification Coupled With Nanoparticle-Based Lateral Biosensor for Rapid, Sensitive, and Specific Detection of Bordetella pertussis - Sun, Chunrong; Xiao, Fei; Fu, Jin; Huang, Xiaolan; Jia, Nan; Xu, Zheng; Wang, Yi; Cui, Xiaodai (Frontiers in Bioengineering and Biotechnology, 2022)
Bordetella pertussisis the most frequently causative agent for pertussis, which is a highly contagious disease. Here, we developed a method based on Loop-mediated isothermal amplification (LAMP) and nanoparticle-based lateral flow biosensor (LFB) for timely diagnosis of B. pertussis infections. A set of 6 primers was designed for LAMP reactions, and the LAMP results were rapidly and visually indicated using LFB. The recommended condition for the B. pertussis-LAMP reactions is 40min at 66°C. Our results confirmed that B. pertussis LAMP-LFB assay could specifically detected Bordetella pertussis, and did not cross-reactwith non-B. pertussis isolates.The sensitivity of B. pertussis-LAMP-LFB was 50 fg per reaction.In particular, 108 nasopharyngeal swab (NPS) samples were applied to evaluate B. pertussis LAMP-LFB assay, and these results were compared with that of qPCR method. The positive rates of B. pertussis-LAMP-LFB and qPCR were 40.7% and 38.8%, respectively, and the agreement between LAMP-LFB and qPCR was 98% with a kappa value of 0.96.The whole process of LAMP-LFB, including rapid template extraction (15 min), LAMP reaction (40 min) and LFB test (within 2 min),can be completed within 1 h, which was more less than qPCR assay. Collectively, B. pertussis LAMP-LFB assay developed in this report offers a new option for rapid, reliable and simple diagnosis of B. pertussis infections.